Optimization of a reverberation chamber performance through different simulated stirrer designs - Bothma, Aneshka (Stellenbosch : Stellenbosch University, 2025)
Bothma, A. 2025. Optimization of a Reverberation Chamber Performance Through Different Simulated Stirrer Designs. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/24ab1567-2fd4-43ac-b6ec-ba2d6d25b720